Relationship Between the Self-Concept of Children and Their Ability to Recognize Emotions in Others - Cordeiro, Teresa; Botelho, Júlia; Mendonça, Catarina (Frontiers in Psychology, 2021)
The study reported here aimed to assess the relationship between children's self-concept and their ability to recognize emotions in others from facial expressions. It is hypothesized that children use their self-representations to interpret depictions of emotion in others and that higher self-concepts might be associated with earlier development of emotion recognition skills. A total of 54 children with ages between 5 and 11 years old participated in the study. Self-concept was assessed in all children with the Piers-Harris Self-Concept Scale for Children (Piers-Harris 2). To assess emotion recognition, a computerized instrument, the Penn Emotion Recognition Task (PERT), was applied. Despite the small sample of children, results show clear statistical effects. It is shown that emotion recognition ability is directly correlated with self-concept for intellectual/school status. The ability to correctly identify emotions from facial expressions is affected by general self-concept, intellectual/school status, and by the stimulus features of gender, intensity and emotion. Further analysis shows that children’s general self-concept particularly affects the ability to identify happy faces. Children with a higher intellectual status score recognize happiness and neutral faces more easily. We conclude that self-concept in children relates to the ability to recognize emotions in others, particularly positive emotions. These findings provide some support to the Simulation Theory of social cognition, where children use their own self-representations to interpret mental states in others. The effect of the self-concept for intellectual status on emotion recognition might also indicate that intellectual abilities act as a mediator between self-concept and emotion recognition, but further studies are needed.